Pattern division random access (PDRA) scheme for mMIMO systems - Xiaoming DAI; Lizhuo PANG; Zheng CHANG; Xinyue ZHANG; Yiran XING; Xiyuan WANG (Dianxin kexue)
To enhance the massive machine-type communications (mMTC) random access (RA) performance, a pattern division random access (PDRA) scheme was proposed for massive multiple-input multiple-output (mMIMO) systems.In this scheme, the pilot contention space was expanded to the pattern-domain.To enlarge the size of contention space without resorting to increasing the physical resources, the pattern-domain pilot was constructed based on the superposition of L cyclically-shifted Zadoff-Chu (ZC) sequences.Simulation results illustrate that the PDRA scheme can reduce pilot collision probability significantly, and improve the access success probability compared with the conventional RA scheme, without compromising excessively on channel estimation and data detection performance.